A new species of Anacaena Thomson, 1859 from the Cederberg Range, South Africa (Coleoptera: Hydrophilidae) - Bilton, David T.; Mlambo, Musa C.; Balke, Michael (Zootaxa, 2025)
Anacaena fosteri sp. nov. is described from a high-altitude bog in the Cederberg, Western Cape Province, South Africa. The new species was collected from temporarily wet algal films over peat and likely lives out of water for much of the year. The habitus, aedeagus, femoral pubescence and habitat of the new species are illustrated, together with details of its ecology.